2017
DOI: 10.1074/jbc.m116.744482
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal mTORC1 Is Required for Maintaining the Nonreactive State of Astrocytes

Abstract: Edited by F. Anne StephensonAstrocytes respond to CNS insults through reactive astrogliosis, but the underlying mechanisms are unclear. In this study, we show that inactivation of mechanistic target of rapamycin complex (mTORC1) signaling in postnatal neurons induces reactive astrogliosis in mice. Ablation of Raptor (an mTORC1-specific component) in postmitotic neurons abolished mTORC1 activity and produced neurons with smaller soma and fewer dendrites, resulting in microcephaly and aberrant behavior in adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…previously shown to suppress astrocyte activation (Kang et al, 2014;Y. Zhang et al, 2017), and our RNA-Seq results revealed that the FGF2 transcript was markedly increased in the hippocampus of FBN-ARO-KO1GCI mice versus FLOX1GCI mice.…”
Section: Depletion Of Forebrain Neuronal E2 Invokes Compromised Astrosupporting
confidence: 69%
See 2 more Smart Citations
“…previously shown to suppress astrocyte activation (Kang et al, 2014;Y. Zhang et al, 2017), and our RNA-Seq results revealed that the FGF2 transcript was markedly increased in the hippocampus of FBN-ARO-KO1GCI mice versus FLOX1GCI mice.…”
Section: Depletion Of Forebrain Neuronal E2 Invokes Compromised Astrosupporting
confidence: 69%
“…RNA-Seq analysis showed increased FGF2 mRNA levels in FBN-ARO-KO mice after GCI, and double immunohistochemistry revealed that the FGF2 protein was significantly elevated in hippocampal neurons in FBN-ARO-KO mice after GCI. Neuron-derived FGF2 has been shown to exert an inhibitory effect on astrocyte activation by suppressing GFAP expression in astrocytes (Reilly et al, 1998;Y. Zhang et al, 2017).…”
Section: Role Of Neuronal Fgf2 In Neuron-derived E2-regulated Astrocymentioning
confidence: 99%
See 1 more Smart Citation
“…However, for neurons, it has already been shown that extent of mTOR hyperactivity correlates with seizure severity and associated neuropathology ( 73 ). Finally, in addition to intrinsic astrocytic properties, maintenance of a non-reactive state in astrocytes was also shown to depend on neuronal mTORC1 signaling, adding yet another level to altered astrocyte function in TSC ( 74 ).…”
Section: Astrocytesmentioning
confidence: 99%
“…5 A and B, compare bar 3 with 1). Suppression of mTORC1 not only disinhibits autophagy but also reduces protein translation, which may independently affect spine morphology and soma body size (35,38,39), and can potentially inhibit cell growth, proliferation, and ribosome biogenesis. To distinguish the contribution of auto- phagy to the rescue of spine morphology, we next delivered lentivirus carrying shRaptor to suppress mTORC1 together with shRNA directed to Atg7 (40)(41)(42), an E1-like ligase essential for autophagosome formation, directly into the CA1 of Fmr1-KO mice to selectively block autophagy (43).…”
Section: Activation Of Autophagy Ameliorates Aberrant Spine Morphologmentioning
confidence: 99%